A pocket guide to scientific writing in aquaculture research - Yossa, Rodrigue (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2022)
"Writing a high-quality scientific aquaculture publication is challenging, and many students and early career aquaculture scientists find the task daunting. Yossa provides new researchers with all the tools they need to write abstracts and a variety of articles (peer-reviewed, technical, magazines, working papers, scientific reports and more). He talks the reader step-by-step through the process of reviewing submitted manuscripts and replying to reviewers, and understanding research ethics. Each section is accompanied by examples, offerings a lifeline to aquaculture students and early career academics getting to grips with the basics."--Provided by publisher.
Chapter 1: -- Introduction -- Chapter 2: -- Principles of scientific writing -- Chapter 3: -- Ethics in scientific writing -- Chapter 4: -- Writing a peer-reviewed original article from abstract to conclusion -- Chapter 5: -- Manuscript submission -- Chapter 6: -- Reviewing a manuscript for a peer-reviewed journal -- Chapter 7: -- Preparing authors' responses to reviewers' and editors' comments -- Chapter 8: -- Writing a research report -- Chapter 9: -- Writing a working paper -- Chapter 10: -- Writing a conference abstract -- Chapter 11: -- Writing an article for conference proceedings -- Chapter 12: -- Writing a technical article for a magazine -- Chapter 13: -- Overview on managing a manuscript writing project -- Chapter 14: -- Practical considerations to improve scientific writing skills -- Chapter 15: -- Conclusion.
Includes bibliographical references and index.
Keywords: Aquaculture -- Research -- Handbooks, manuals, etc; Technical writing -- Handbooks, manuals, etc